Τέσσερις νέες επιγραφές από την Έδεσσα και την Αλμωπία - Χρυσοστόμου, Αναστασία (Tekmeria, 2013)
Two new inscribed tombstones, dating from the Roman and Early Christian periods, were found in the Agios Nikolaos area in the lower town of ancient Edessa and were added to the already substantial local collection. Inscription no. 1 introduces a new Roman family, while inscription no. 2 acquaints us with the soldier Ioannis from the unit of Secundani, who was also an actuarius. Another Roman family, this time from the southern Almopia, is presented in inscription no. 3. The inscription was subsequently broken in two parts which formed the west and east wall of a Late Roman tomb. Three additional marble pieces originating from the same pedestal were also used to cover the tomb. Apart from the family members, the inscription also introduces Kointos Neikonois, a citizen of Edessa, who was responsible for the construction of the pedestal. <span style="font-size: 10.0pt; font-family: Gentium; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EL; mso-bidi-language: AR-SA;" lang="EN-US">Finally, inscription no. 4, which is the oldest one, comes from an important settlement north of the modern village of Neromyloi in northeastern Almopia; it dates to the Hellenistic Age and refers to the erection of an altar.